2018
DOI: 10.21037/jtd.2018.10.105
|View full text |Cite
|
Sign up to set email alerts
|

Hematological indices as simple, inexpensive and practical severity markers of obstructive sleep apnea syndrome: a meta-analysis

Abstract: Background: Clinical detection of inflammatory markers is useful to assess the degree of nocturnal hypoxia and predict the presence of complications in obstructive sleep apnea syndrome (OSAS) patients. Nowadays, some researchers proposed that hematological parameters could be substituted for novel diseasespecific biochemical markers (such as C-reactive protein) because they were comparatively cheap, simple and practical. But there was a contradiction whether the hematological parameters were positively correla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 66 publications
(101 reference statements)
2
27
2
3
Order By: Relevance
“…Interestingly, the hematocrit level is also correlated with OSA severity. This correlation has been previously identified in individuals in the overall population with OSA[35,36]; however, this finding had not yet been demonstrated in the population of adult individuals with DS. This correlation possibly reflects the presence and greater severity of nocturnal hypoxemia that stimulates increased erythropoietin synthesis, with consequent elevated erythrocyte production and increased hematocrit levels[35,36].…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, the hematocrit level is also correlated with OSA severity. This correlation has been previously identified in individuals in the overall population with OSA[35,36]; however, this finding had not yet been demonstrated in the population of adult individuals with DS. This correlation possibly reflects the presence and greater severity of nocturnal hypoxemia that stimulates increased erythropoietin synthesis, with consequent elevated erythrocyte production and increased hematocrit levels[35,36].…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, the hematocrit level is also related with OSA severity (REI). This relation has been previously identified in individuals in the overall population with OSA [36,37]; however, it had not yet been demonstrated in the population of DS adults. This relation possibly reflects the presence and greater severity of nocturnal hypoxemia that stimulates increased erythropoietin synthesis, with consequent elevated erythrocyte production and increased hematocrit levels [36,37].…”
Section: Discussionmentioning
confidence: 56%
“…11 To date, only a few studies have examined the association between OSA and erythrocyte measures. [12][13][14][15][16] Choi et al 13 found that patients with severe OSA had higher hematocrit and hemoglobin than patients without OSA and patients with mild-to-moderate OSA, but red blood cell count was not reported. Conversely, other studies did not find any associations between OSA severity and hematocrit or hemoglobin level, 12,14,15 although 1 study found significant differences in red blood cell count among different OSA severity groups.…”
Section: Introductionmentioning
confidence: 99%